Letters to Attawapiskat - MacDonald, Michael B.; Cipher5 (My University, 2016)
The story of tragedy at the Attawapiskat First Nations brings up issues of colonization, truth and reconciliation in a very personal way for a group of hiphoppas in Edmonton, Alberta, Canada. A film by Michael B. MacDonald; A CIPHER5 Production; 31:11 minutes. Retrieved from: http://www.michaelbmacdonaldfilms.ca/
Keywords: First Nations; social conditions